Neutrophil extracellular traps-mediated Beclin-1 suppression aggravates atherosclerosis by inhibiting macrophage autophagy - Sano, Masataka; Maejima, Yasuhiro; Nakagama, Shun; Shiheido-Watanabe, Yuka; Tamura, Natsuko; Hirao, Kenzo; Isobe, Mitsuaki; Sasano, Tetsuo (Frontiers in Cell and Developmental Biology, 2022)
A growing body of evidence suggests that neutrophil extracellular traps (NETs) critically contribute to the development of atherosclerosis. However, the detailed mechanism of how NETs promote atherogenesis remains unknown. In this study, we explored the role of NETs for promoting atherosclerosis by modulating the activity of autophagy in macrophages. NETs were effectively induced by a nicotine administration to the HL-60 cell-derived neutrophil-like cells. Treatment with NETs markedly suppressed both autophagosome formation and autophagosome–lysosome fusion in 7-ketocholesterol-treated macrophages, which are accompanied by the enhancement of inflammasome activity. NETs upregulate epidermal growth factor receptor (EGFR) activity, which enhances Beclin-1 phosphorylation of the tyrosine residues of Beclin-1 by EGFR, inhibits the PI3 kinase activity of the Beclin1–Vps34 complex, and suppresses autophagosome formation in macrophages. Furthermore, NET-induced activation of EGFR allows Rubicon to increase its expression, thereby suppressing autophagosome–lysosome fusion. In vivo experiments revealed that the suppression of NET formation by ablating peptidyl arginine deiminase-4 in neutrophil leukocytes resulted in the attenuation of atherosclerotic plaques in a nicotine-administered HFD-fed ApoE–/–mice. Taken together, these results suggest that NET-mediated EGFR–Beclin-1 signaling in the macrophages promotes atherogenesis by autophagy inhibition-mediated inflammasome activation.